Mass balance of the Nezhdanny and Sosedny glaciers of the Koryak Highlands in 1961–2016 - G. A. Nosenko; A. Ya. Muraviev; S. A. Nikitin (Лëд и снег, 2022)
The Koryak Highland is one of the areas of the present-day mountain glaciation in the north-east of the Asian part of Russia. Its remoteness and inaccessibility are serious obstacles to the ground-based (field) researches, so our knowledge of the regime of glaciers in this area is still incomplete. Objective of this study was to obtain data on changes in the state of glaciers for about a half-century period. For this purpose, the following information was used: results of ground-based phototheodolite surveys of two glaciers on the Ledyanaya Mountain massif (2,453 m) in the central part of the highland, carried out in August 1961 by the expedition of the Institute of Geography of the USSR Academy of Sciences, data from recent space surveys SPOT 6, and a digital relief model ArcticDEM v3.0 2016. The glaciers under investigation are Nezhdanny and Sosedniy. Using these data, the mass balance of glaciers was estimated by the geodetic method. It was found that for 55 years, the area of glaciers decreased by 0.75 km2 (15.2%), the volume – by 71.74 ± 16.51 million m3, and the average lowering in height of the surface – 16.7 m. For the period 1961–2016 the average annual specific mass balance of glaciers was equal to –0.362 ± 0.065 m w.e. yr−1. In this region the main factors exerting influence upon changes in the size of glaciers are the following: first, the summer air temperature rise of about 2 °C since the end of the twentieth century, and the second, a decrease in the amount of solid precipitation by 0.15 m w.e. per year. Degradation of glaciers is caused by changes in conditions of glacial alimentation, increased ablation, and the active cryogenic factors. At the same time, a new rock glacier is being formed in the alimentation area. It is possible that in the future the new one will replace the degrading glacier.